Thinking through the Prospects of the Integration of Bioengineering and Artificial Intelligence - Duhao Chen; Yuanyuan Tian (Proceedings, 2022)
The continuous progress of the two technologies of bioengineering and artificial intelligence has further expanded the depth and breadth that can be achieved through technological integration between the two. Along with the bright prospects of new technologies come worries about the risks of technology applications, but as long as technology integration upholds certain practical principles, it will open up a new path for the future development of bioengineering and artificial intelligence. This will also provide new opportunities for the development of mankind and society.